2012
DOI: 10.1080/02687038.2012.654933
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of connected speech in semantic dementia vs Alzheimer's disease

Abstract: Background: Neurodegenerative syndromes are associated with varying degrees of language impairment. Connected speech analysis provides the most realistic measure of language function but its use has been restricted by operational constraints. Aims: In this prospective study we assessed the relative utility of a picture description task and a semi-structured interview in exposing the language decline in semantic dementia (SD) and typical mild Alzheimer's disease (AD), compared to each other and to healthy volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
127
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(155 citation statements)
references
References 51 publications
15
127
0
3
Order By: Relevance
“…Other features in this domain have been rarely or inconsistently reported across studies; see Supplementary Table 3 for a complete list. Although, several studies agree in considering syntactic processes preserved in persons with AD (Kavé and Levy, 2003; Forbes-McKay and Venneri, 2005), a consistent number of the studies included in this review report a simplification of syntax, characterized by reduced sentences and short utterances (Ash et al, 2007; de Lira et al, 2011; Sajjadi et al, 2012a; Orimaye et al, 2014; Ash and Grossman, 2015; Yancheva et al, 2015). …”
Section: Results: Relevant Features and Linguistic Profiles Of The Mamentioning
confidence: 71%
See 1 more Smart Citation
“…Other features in this domain have been rarely or inconsistently reported across studies; see Supplementary Table 3 for a complete list. Although, several studies agree in considering syntactic processes preserved in persons with AD (Kavé and Levy, 2003; Forbes-McKay and Venneri, 2005), a consistent number of the studies included in this review report a simplification of syntax, characterized by reduced sentences and short utterances (Ash et al, 2007; de Lira et al, 2011; Sajjadi et al, 2012a; Orimaye et al, 2014; Ash and Grossman, 2015; Yancheva et al, 2015). …”
Section: Results: Relevant Features and Linguistic Profiles Of The Mamentioning
confidence: 71%
“…The picture description task is reported as more suitable in detecting lexico-semantic disorders, while the semi-structure interview was more sensitive in revealing impairment affecting the morphological, syntactic, and discourse levels (Sajjadi et al, 2012a,b). A third study however reported that the story narration and the picture description can be used interchangeably (Ash et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported syntactic impairments in AD, while others claim that any apparent deficits are in fact due to difficulties with memory and semantics [18]. Several studies have found evidence for a decrease in the syntactic complexity of language in AD [34][35][36]. Croisile et al [34] compared oral and written picture descriptions from 22 AD patients and matched controls, and found that the AD patients produced fewer subordinate clauses than controls.…”
Section: Introductionmentioning
confidence: 99%
“…For example, picture description reveals semantic impairments (as in Kavé & Levy, 2003), but free speech produced during a semi-structured interview may be better suited for exposing morphosyntactic processing deficits (Sajjadi, Patterson, Tomek, & Nestor, 2012). Although a large number of studies have attempted to characterize linguistic impairments in AD, relatively few have considered if and how speech errors might be elicited as a possible diagnostic tool.…”
mentioning
confidence: 99%